Effect of lactic acid bacteria, yeast, and their mixture on the chemical composition, fermentation quality, and bacterial community of cellulase-treated Pennisetum sinese silage - Liao, Chaosheng; Tang, Xiaolong; Li, Maoya; Lu, Guangrou; Huang, Xiaokang; Li, Lin; Zhang, Mingjie; Xie, Yixiao; Chen, Chao; Li, Ping (Frontiers in Microbiology, 2022)
The present study investigated the effects of lactic acid bacteria, yeast, and a mixture of the two on the cellulose degradation and microbial community of cellulase-treated Pennisetum sinese (CTPS) during biological pretreatment. The CTPS was stored without (CK) or with Lentilactobacillus buchneri (L), yeast (Y, Saccharomyces cerevisiae), and their mixture (LY) under anaerobic conditions for 60 days. All inoculants enhanced the anaerobic fermentation of CTPS. In relative to L, inoculations with Y and LY decreased the cellulose level of fermented-CTPS by 8.90~17.13%. Inoculation with L inhibited the growth of Weissella cibaria during anaerobic storage. However, inoculations with LY increased the relative abundance of the homofermentative bacterium Lactiplantibacillus plantarum by 6.04%. Therefore, inoculating yeast reduced the adverse effects of L. buchneri-stimulated fermentation on cellulose degradation by altering the bacterial community during anaerobic storage of P. sinese. This work provides a new insight for the subsequent anaerobic digestion of P. sinese.